Diversification of European Union Member States Due to the Production of Renewable Energy from Agriculture and Forestry - Dorota Janiszewska; Luiza Ossowska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The main objective of this article is to discuss the diversity of European Union countries in terms of their production of renewable energy from agriculture and forestry. The analysis includes 28 EU countries. Figures come from 2013-2015. Diversification of European Union members was conducted using cluster analysis. The following diagnostic features were used for the analysis: production of renewable energy from agriculture, share of agriculture in production of renewable energy, change in the production of renewable energy from agriculture in 2013-2015, production of renewable energy from forestry, share of forestry in production of renewable energy, change in the production of renewable energy from forestry in 2013-2015. As a result of the cluster analysis examined regions were divided into five groups.